Bóg - ״budowniczy Izraela"1 i Kościoła. Przesłanie Rdz 2,18-24 w świetle tajemnicy paschalnej Chrystusa - Sulowski, Julian (Poznańskie Studia Teologiczne, 2008)
This article aims mainly at revealing the spiritual sense of the pericope according to wording of the Papal Biblical Commission: the spiritual sense conceived according to Christian faith, as sense expressed through biblical texts, when they are read under the influence of Holy Spirit in the context of paschal mystery of Christ and the new life springing from it. JHWH is expressed in the words: It is not good for the man to be for himself (Gen. 2,18a). In BHS there is a particle of purpose 19, for, in purpose of, overlooked by exegetes in a Hebrew word hbaddó, consisting of a particle of purpose 19, a noun bad = separation, a part of, and a pronoun suffix 6. That is why the standard translation of this verse should be changed (istead to be alone, for to be for himself). ‘The man-Adam, being alone, not having any relation to anybody else, was not yet image of God’ (Kiemikowski), because ‘God is love’ in the relation of the three divine persons, and because it is said in Gn 1,27 that woman and man were created together in God«s image and the word 3àdam means both man and woman (1,26). The deepest carrier of the message of the pericope is the verb banah - built, occuring here in the form of wajjiqtol wayylben. It is full of meaning that the theme of God as a builder or an architect in himself appears in the exile or post-exile texts Is 45,13; 62,5; lKgs 11,39; Jer 5,5n; 31,2-6; Ez 36,33-38; Ps 102,17; 127,1; 147,2. Biblical authors use a verb ״bnh”- to build because a conception and birth of the man was always related to activity of God who ‘was building’ man in his mother's womb (Gn 16,2; 30,5; Ps 139,13), who was building a dynasty (2 Sm 7,27; 1 Kgs 17,25), and consequently he was building the nation and the state, (cf. Ex 1,21 Dt 25,9). The following conlusions result from this article: 1. The key to understanding the pericope is the allusion of the verse Gn 2,23a to the formula of the covenant (W. Briiggemann), which does not say about origin of the woman in a biological sense. Exegetical tradition interpreting the text as supposedly saying about the biological origin of the woman is based on familiarization of the word ‘rib’ and with inappropriate play of words in 23b, which blurrs and misinterpretes the meaning of the text. While the main intention of the text is to emphasize solidarity of man and woman and their mutual responsibilty for each other and for the world. 2. This solidarity is mutual but it refers both to cultivating soil - 3àdàmàh (3iSSah - 5adama11) and to observing the Law of the covenant. 3. Image of God and his bride Israel is close to the prophets.That is why Gn 2,18-24 refers to the teachings of the prophets about the covenant (H. Renckens), especially to Hos 1-3; Ez 16 i 23; Deutero- i Trito-Isaiah. This image was presented both in terms of infidelity and restored relations of the covenant. The metaphor of marriage says about the covenant of God with Israel. However, on basis of Gn 2,23a it is clear that this marriage is not a more personal or auxiliary image of the covenant but speaks directly about permanent relations which last between God and Israel in weal and woe, in weakness and power, in faithfulness and infidelity. 4. The same imagery is used by St. Paul in Eph 5,21-33. The relation between Christ and Church was built on the community of fate, loyalty and responsibility which has a guarantee to survive in any lot. Christ and Church are one body. This is a formula of the covenant repeated by Paul from Gn 2,24. The words of St. Paul His purpose for dying for all was that men, while still in life, should cease to live for themselves, and and should live for him, whofor their sake died and was raised to life (2C0r 5,15) are found as a prolongation of Gn 2,18 It is not good for the man to be for himself. 5. The text does not suggest any superiority of male element over female or justifies sexual intercourses since such a problem did not exist in Israel. Marriage was based on community of fate, loyalty and commitment which ought to be treated seriously. It is neither light nor accidental, grounded on mood or feeling. It is based on an oath of solidarity. Its general aim is not tofind mutual joy, though not excluded, but it is the job of cultivating soil and obeying the Law of the covenant. Thus, human relations were grasped in context of solidarity and responsibility for people and the world.